2000
DOI: 10.1051/aas:2000184
|View full text |Cite
|
Sign up to set email alerts
|

Tuorla quasar monitoring

Abstract: Abstract. We present results of optical monitoring of quasars and blazars obtained at Tuorla Observatory between September 1995 and May 1997. The aim of our monitoring is to provide well sampled optical light curves for quasar and blazar studies. During the observing period the V -band brightness of S2 0109+224, 3C 66A, and ON 231 (W Comae) reached some of the brightest values ever measured for these objects. A strong outburst was observed in Mrk 421 and the large outburst, which was predicted earlier, in OJ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 52 publications
(95 reference statements)
7
56
0
Order By: Relevance
“…However, occasional sharp flares have also been observed in CTA 102. Variations as high as ∆B = 1. m 07 in 2 days [4] and ∆V = 1. m 13 in 3 days [6] were observed in 1978 and 1996, correspondingly. The previously reported historical maximum for the object, R ≈ 14. m 5, was reached on Oct. 4, 2004 during a short-term event accompanied by prominent intranight variability [7].…”
Section: Introductionmentioning
confidence: 84%
“…However, occasional sharp flares have also been observed in CTA 102. Variations as high as ∆B = 1. m 07 in 2 days [4] and ∆V = 1. m 13 in 3 days [6] were observed in 1978 and 1996, correspondingly. The previously reported historical maximum for the object, R ≈ 14. m 5, was reached on Oct. 4, 2004 during a short-term event accompanied by prominent intranight variability [7].…”
Section: Introductionmentioning
confidence: 84%
“…Some periods obtained in this study, for the well-observed BL Lacertae object B0716+714, are already known. A period of 68 days is mentioned by Katajainen et al (2000), and a period of three years is mentioned by Raiteri et al (2003). For the BL Lac object B1215+303, two periods of 4.45 and 6.89 yr are mentioned by Fan et al (2002).…”
Section: Periodogram Analysis Of the Observational Datamentioning
confidence: 99%
“…Webb et al (1998), Bai et al (1999), Tosti et al (1999), Ghosh et al (2000), Katajainen et al (2000), Clements & Carini (2001), Fan et al (2001), Sobrito et al (2001), Papadakis et al (2003), Tosti et al (2004).…”
Section: Observations Of Bl Lacertae By the Webt Collaborationmentioning
confidence: 99%